A critical review on clay-based nanocomposite particles for application of wastewater treatment. (5th May 2022) - Ayalew, Adane Adugna
Abstract: Nanotechnology plays an important function in recent environmental aspects for the elimination of contaminants in the ecosystem. In recent times, nano-clay has initiated more concentration because of its distinctive physicochemical properties and characteristics. Recently, many types of research in clay-based nanocomposite were accomplished in the elimination of pollutants from water sources. Nanocomposite materials have advanced properties useful for contaminat removal such as higher surface area, thermal stability, selectivity to remove different contaminants, improved process ability, and fast decontamination. Thus, the development of clay-based composite materials is one of the upcoming directions to use effectively in water and wastewater treatment as adsorbent nanomaterials. This paper assesses the latest achievement in clay-based nanocomposite preparation, material property analysis and function for various pollutant removals. In particular, great consideration was paid to the recent progress in clay/metallic, clay-polymer, and clay-carbon composites presenting their application in the removal of different kinds of pollutants. Moreover, the mechanism of adsorption, the challenges and future perspective were also discussed to reach the optimum performance of the nanomaterials adsorbent. It is confirmed that clay-based nanocomposite materials are more cost-effective technology than conventional treatment methods. HIGHLIGHTS: Nanocomposite materials have advanced properties useful for contaminate removal. Clay based nanocomposite can overcome the restrictions of individual clay and other constituents such as low selectivity, pH dependency, small specific surface area, and low water wettability. Clay based nanocomposite can be utilized as a cost-effective and novel adsorbent for the adsorption of organic contaminants from water and wastewater.